Polymer electrolyte membrane and preparation method and application thereof

By adding metal organic acid salts to the polymer electrolyte slurry and using an external magnetic field for directional migration, an enriched polymer electrolyte membrane and lithium metal interface gradient SEI is formed, which solves the problems of poor ion transport performance and high interface impedance at the solid electrolyte/lithium metal interface, and achieves the effect of high ionic conductivity and low interface impedance.

CN120767407APending Publication Date: 2025-10-10HARBIN INST OF TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510968633.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-15
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

The ion transport performance of the solid electrolyte/lithium metal interface is poor and the interface impedance is high.

Method used

By adding metal organic acid salts as functional fillers to the polymer electrolyte slurry and coating them on the template under the action of an external magnetic field, the metal ions are induced to migrate and arrange in a directional manner to form an enriched polymer electrolyte membrane. Combined with lithium metal pressing, a gradient SEI is formed to optimize the interface structure.

Benefits of technology

It improves the ionic conductivity of the polymer electrolyte membrane, improves the ion transport performance of the solid electrolyte/lithium metal interface, reduces the interface impedance, and improves the cycle performance of the solid-state lithium battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120767407A_ABST
    Figure CN120767407A_ABST
Patent Text Reader

Abstract

The invention provides a polymer electrolyte membrane and a preparation method and application thereof, and relates to the technical field of battery materials, the preparation method of the polymer electrolyte membrane comprises the following steps: dissolving a polymer, a metal organic acid salt, a plasticizer and a lithium salt in an organic solvent to obtain a polymer electrolyte slurry; coating a template with the polymer electrolyte slurry, performing standing treatment under the action of an external magnetic field, and performing vacuum drying treatment to obtain a polymer electrolyte membrane; wherein the direction of the external magnetic field is perpendicular to the template. The polymer electrolyte membrane provided by the invention is used for modifying lithium metal, so that not only can the ion transmission performance of a solid electrolyte / lithium metal interface be improved, but also the interface impedance of the solid electrolyte / lithium metal interface can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a polymer electrolyte membrane and a preparation method and application thereof. Background Art

[0002] Against the backdrop of an urgent need for high-energy-density, long-life energy storage systems, solid-state lithium batteries have become a core development direction for next-generation battery technology due to the intrinsic safety of solid-state electrolytes and their high theoretical energy density compatible with lithium metal anodes. However, the compatibility problem at the interface between solid-state electrolytes and lithium metal has severely restricted the performance improvement and commercialization of solid-state lithium batteries. From both thermodynamic and kinetic perspectives, this contradiction stems from the high chemical activity of lithium metal and the high energy barrier to ion transport at the solid-state electrolyte / lithium metal interface. Specifically, the following are the main manifestations: First, the solid-state electrolyte / lithium metal interface is unstable, and the SEI film formation process is highly random, making it difficult to achieve precise control of its chemical composition and microstructure. This results in insufficient ion conductivity and weak mechanical strength of the SEI film formed at the interface, resulting in poor ion transport performance at the solid-state electrolyte / lithium metal interface. Second, the interface impedance of the solid-state electrolyte / lithium metal interface is high, and the resistive interface layer formed by physical contact defects and continuous side reactions between the interfaces severely hinders ion transport. Summary of the Invention

[0003] The present invention solves at least one of the following problems: (1) poor ion transport performance at the solid electrolyte / lithium metal interface; (2) high interfacial impedance at the solid electrolyte / lithium metal interface.

[0004] To solve the above problems, the present invention provides a method for preparing a polymer electrolyte membrane, comprising: Step S1, dissolving a polymer, a metal organic acid salt, a plasticizer and a lithium salt in an organic solvent to obtain a polymer electrolyte slurry; Step S2: coating the polymer electrolyte slurry on a template, allowing it to stand under an external magnetic field, and then performing vacuum drying to obtain a polymer electrolyte membrane; wherein the direction of the external magnetic field is perpendicular to the template.

[0005] Optionally, in step S1, the mass ratio of the polymer, the metal organic acid salt, the plasticizer and the lithium salt is (95 to 100): (8 to 12): (18 to 22): (30 to 40).

[0006] Optionally, in step S1, the metal ions in the metal organic acid salt include Mg 2+ 、Al 3+ 、In 3+ 、Zn 2+ 、Ag+ 、Sn 4+ 、Au + , Pt + 、Ge 4+ 、Bi 3+ and Sb 3+ At least one of; the organic acid radical in the metal organic acid salt includes at least one of sulfonate, fluorosulfonate, trifluoromethanesulfonate, fluorosulfonimide, tris(pentafluorophenyl)borate and tris(trifluoromethyl)borate.

[0007] Optionally, in step S1, the polymer includes at least one of polyethylene oxide, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, polyvinyl chloride, polyurethane and polyimide.

[0008] Optionally, the plasticizer includes at least one of succinonitrile, adiponitrile, glutaronitrile, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, N-butyl-N-methylpyrrolidine bis(fluorosulfonyl)imide salt, tetraethylammonium trifluoromethanesulfonate, ethylene carbonate, propylene carbonate, fluoroethylene carbonate, diethylene glycol dimethyl ether, perfluoropolyether and polyethylene glycol dimethyl ether.

[0009] Optionally, in step S1, the lithium salt includes at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium trifluoromethylsulfonate, lithium dioxalatoborate and lithium difluorooxalatoborate.

[0010] Optionally, in step S2, the magnitude of the external magnetic field is 0.1T to 0.5T.

[0011] Optionally, in step S2, the standing treatment time is 10 hours to 14 hours, and the vacuum drying treatment temperature is 50° C. to 70° C., and the time is 10 hours to 14 hours.

[0012] The present invention also provides a polymer electrolyte membrane, which is manufactured by the above-mentioned method for manufacturing a polymer electrolyte membrane.

[0013] The present invention also provides an application of the polymer electrolyte membrane as described above, comprising: pressing the polymer electrolyte membrane and lithium metal together to obtain modified lithium metal.

[0014] Compared with the related art, the application facilitates to improve the ionic conductivity of the polymer electrolyte membrane by adding metal organic acid salt as a functional filler into the polymer electrolyte slurry, after the polymer electrolyte slurry is coated on a template, the metal ions in the polymer slurry are induced to migrate and arrange directionally by an external magnetic field perpendicular to the template, the metal ions are preferentially enriched on one surface of the polymer electrolyte membrane under the driving action of the magnetic field, the organic acid ion in the polymer electrolyte slurry generates a solid-state electrolyte interface phase rich in fast ion conductor at the other surface of the polymer electrolyte membrane, so as to realize the precise regulation of the chemical composition and microstructure of the polymer electrolyte membrane, and facilitate to obtain the polymer electrolyte membrane with high ionic conductivity. The polymer electrolyte membrane is pressed together with the lithium metal, so that the surface of the polymer electrolyte membrane where the metal ions are enriched is close to the lithium metal, thereby the lithium metal is alloyed and modified, and the polymer electrolyte membrane is located between the solid-state electrolyte and the lithium metal during use, so as to form a gradient SEI between the solid-state electrolyte and the lithium metal, which is not only beneficial to improve the ion transmission performance of the solid-state electrolyte / lithium metal interface, but also beneficial to reduce the interface impedance between the solid-state electrolyte and the lithium metal. BRIEF DESCRIPTION OF DRAWINGS

[0015] Figure 1 The scanning electron microscope picture of the lithium metal surface after 100 charge-discharge cycle tests of the solid-state lithium battery prepared in Example 1; Figure 2 The scanning electron microscope picture of the lithium metal surface after 100 charge-discharge cycle tests of the solid-state lithium battery prepared in Comparative Example 1. DETAILED DESCRIPTION

[0016] In order to make the above objectives, features and advantages of the present application more apparent, more comprehensible, the specific embodiments of the present application will be described in detail below with reference to the accompanying drawings. Although some embodiments of the present application are shown in the drawings, it should be understood that the present application can be implemented in various forms, and should not be interpreted as being limited to the embodiments set forth herein, on the contrary, these embodiments are provided for a more thorough and complete understanding of the present application. It should be understood that the drawings and embodiments of the present application are only for exemplary purposes, and are not intended to limit the scope of protection of the present application.

[0017] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used in the specification of the present application is only for the purpose of describing the specific embodiments and is not intended to limit the present application.

[0018] The term "including" and its variations used in this document are open inclusions, that is, "including but not limited to"; the term "based on" means "at least partially based on"; the term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one other embodiment"; the term "some embodiments" means "at least some embodiments"; the term "optionally" means "optional embodiments". The relevant definitions of other terms will be given in the following description. It should be noted that the concepts of "first" and "second" mentioned in the present invention are used to distinguish different objects, rather than to describe a specific order or a primary and secondary relationship. In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "multiple" means two or more.

[0019] It should be noted that the direction of the external magnetic field is perpendicular to the template, which should be understood as the direction of the external magnetic field being perpendicular to the plane where the template contacts the polymer electrolyte slurry, or the direction of the external magnetic field being perpendicular to the final polymer electrolyte membrane.

[0020] An embodiment of the present invention provides a method for preparing a polymer electrolyte membrane, comprising: Step S1, dissolving a polymer, a metal organic acid salt, a plasticizer and a lithium salt in an organic solvent to obtain a polymer electrolyte slurry; Step S2: coating the polymer electrolyte slurry on a template, allowing it to stand under an external magnetic field, and then performing vacuum drying to obtain a polymer electrolyte membrane; wherein the direction of the external magnetic field is perpendicular to the template.

[0021] The embodiment of the present invention helps to improve the ionic conductivity of the polymer electrolyte membrane by adding metal organic acid salts as functional fillers to the polymer electrolyte slurry. After the polymer electrolyte slurry is coated on the template, the metal ions in the polymer slurry are induced to migrate and arrange in a directional manner through an external magnetic field perpendicular to the template. Under the driving action of the magnetic field, the metal ions are preferentially enriched at one of the surfaces of the polymer electrolyte membrane, and the organic acid radical ions in the polymer electrolyte slurry generate a solid electrolyte interface phase rich in fast ion conductors at the other surface of the polymer electrolyte membrane, thereby achieving precise control of the chemical composition and microstructure of the polymer electrolyte membrane, which is conducive to obtaining a polymer electrolyte membrane with higher ionic conductivity.

[0022] In some embodiments of the present invention, in step S1, the mass ratio of the polymer, the metal organic acid salt, the plasticizer and the lithium salt is (95 to 100): (8 to 12): (18 to 22): (30 to 40).

[0023] In some embodiments of the present invention, in step S1, the metal ions in the metal organic acid salt include Mg 2+ 、Al 3+ 、In 3+ 、Zn 2+ 、Ag + 、Sn 4+ 、Au + , Pt + 、Ge 4+ 、Bi 3+ and Sb 3+ At least one of; the organic acid radical in the metal organic acid salt includes at least one of sulfonate, fluorosulfonate, trifluoromethanesulfonate, fluorosulfonimide, tris(pentafluorophenyl)borate and tris(trifluoromethyl)borate.

[0024] In some embodiments of the present invention, in step S1, the polymer includes at least one of polyethylene oxide, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, polyvinyl chloride, polyurethane and polyimide.

[0025] In some embodiments of the present invention, the plasticizer includes at least one of succinonitrile, adiponitrile, glutaronitrile, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, N-butyl-N-methylpyrrolidino bis(fluorosulfonyl)imide, tetraethylammonium trifluoromethanesulfonate, ethylene carbonate, propylene carbonate, fluoroethylene carbonate, diethylene glycol dimethyl ether, perfluoropolyether and polyethylene glycol dimethyl ether.

[0026] In some embodiments of the present invention, in step S1, the lithium salt includes at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium trifluoromethylsulfonate, lithium dioxalatoborate and lithium difluorooxalatoborate.

[0027] In some embodiments of the present invention, in step S1, the organic solvent includes at least one of anhydrous acetonitrile, acetone, tetrahydrofuran, N,N-dimethylformamide, dimethyl sulfoxide and N-methylpyrrolidone.

[0028] In some embodiments of the present invention, in step S2, the template is made of polytetrafluoroethylene.

[0029] In some embodiments of the present invention, in step S2, the magnitude of the external magnetic field is 0.1T to 0.5T.

[0030] In some embodiments of the present invention, in step S2, the standing treatment time is 10 hours to 14 hours, and the vacuum drying treatment temperature is 50° C. to 70° C., and the time is 10 hours to 14 hours.

[0031] An embodiment of the present invention further provides a polymer electrolyte membrane, which is manufactured using the above-mentioned method for manufacturing a polymer electrolyte membrane.

[0032] An embodiment of the present invention further provides an application of the polymer electrolyte membrane as described above, comprising: pressing the polymer electrolyte membrane and lithium metal together to obtain modified lithium metal.

[0033] In an embodiment of the present invention, the polymer electrolyte membrane and lithium metal are pressed together, bringing the metal ion-rich surface of the polymer electrolyte membrane closer to the lithium metal, thereby alloying and modifying the lithium metal. During use, the polymer electrolyte membrane is positioned between the solid electrolyte and the lithium metal. The presence of the alloy phase and the lithium fast ion conductor generated by the decomposition of organic acid radical ions can form a gradient SEI between the solid electrolyte and the lithium metal, which not only improves the ion transport performance at the solid electrolyte / lithium metal interface, but also helps reduce the interfacial impedance between the solid electrolyte and the lithium metal.

[0034] An embodiment of the present invention further provides a lithium metal negative electrode, which is manufactured using the above-mentioned method for preparing a lithium metal negative electrode.

[0035] The present invention is further described below with reference to specific embodiments.

[0036] Example 1 A1. Dissolve a polymer, a metal organic acid salt, a plasticizer and a lithium salt in an organic solvent to obtain a polymer electrolyte slurry; wherein the mass of the polymer is 1 g, the mass of the metal organic acid salt is 0.1 g, the mass of the plasticizer is 0.2 g, and the mass of the lithium salt is 362 mg; wherein the polymer is polyethylene oxide, the metal organic acid salt is Al(CF3SO3)3, the plasticizer is succinonitrile, and the lithium salt is lithium bis(trifluoromethanesulfonyl imide); the organic solvent is anhydrous acetonitrile, and the amount used is 25 ml.

[0037] A2. The polymer electrolyte slurry is coated on a template, allowed to stand under an external magnetic field, and then vacuum dried to obtain a polymer electrolyte membrane; wherein the direction of the external magnetic field is perpendicular to the template, the template is made of polytetrafluoroethylene, the thickness of the polymer electrolyte membrane is 20 μm, the magnitude of the external magnetic field is 0.3 T, the standing time is 12 h, the temperature of the vacuum drying treatment is 60°C, and the time is 12 h.

[0038] A3. Pressing the polymer electrolyte membrane and lithium metal together by hot isostatic pressing to obtain lithium metal modified by gradient SEI.

[0039] A4, gradient SEI modified lithium metal as negative electrode, LiNi 0.8 Co 0.1 Mn 0.1 O2 is used as the positive electrode active material and Li6PS5Cl is used as the solid electrolyte to assemble an all-solid-state lithium battery.

[0040] Example 2 The difference from Example 1 is that in step A1, the metal organic acid salt is Sn(CF3SO3)3.

[0041] Example 3 The difference from Example 1 is that in step A1, the polymer is polyvinylidene fluoride, the metal organic acid salt is AgN(SO2F)2, the plasticizer is ethylene carbonate, and the organic solvent is N,N-dimethylformamide.

[0042] Example 4 The difference from Example 1 is that in step A1, the polymer is polyurethane, the metal organic acid salt is Zn(CHF2O2S)2, and the plasticizer is succinonitrile.

[0043] Comparative Example 1 Unmodified lithium metal as negative electrode, LiNi 0.8 Co 0.1 Mn 0.1 O2 is used as the positive electrode active material and Li6PS5Cl is used as the solid electrolyte to assemble an all-solid-state lithium battery.

[0044] Comparative Example 2 A polymer, a plasticizer, and a lithium salt are dissolved in an organic solvent to obtain a polymer electrolyte slurry; wherein the mass of the polymer is 1 g, the mass of the plasticizer is 0.2 g, and the mass of the lithium salt is 362 mg; wherein the polymer is polyethylene oxide, the plasticizer is succinonitrile, and the lithium salt is lithium bis(trifluoromethanesulfonyl)imide; and the organic solvent is anhydrous acetonitrile, and the amount used is 25 ml.

[0045] The polymer electrolyte slurry is coated on a template, allowed to stand under the action of an external magnetic field, and then vacuum dried to obtain a polymer electrolyte membrane; wherein, the direction of the external magnetic field is perpendicular to the template, the material of the template is polytetrafluoroethylene, the thickness of the polymer electrolyte membrane is 20 μm, the magnitude of the external magnetic field is 0.3 T, the standing time is 12 hours, and the temperature of the vacuum drying treatment is 60°C and the time is 12 hours.

[0046] The polymer electrolyte membrane and the lithium metal are pressed together by a hot isostatic pressing method in a top-to-bottom arrangement to obtain a polymer electrolyte membrane modified lithium metal.

[0047] The polymer electrolyte membrane modified lithium metal is used as a negative electrode, LiNi 0.8 Co 0.1 Mn 0.1 O2 is used as a positive electrode active material, and Li6PS5Cl is used as a solid-state electrolyte to assemble a full-solid-state lithium battery.

[0048] Comparative Example 3 The difference from Example 1 is that the metal inorganic acid salt in step A1 is replaced by a metal organic acid salt, which is AlBr3.

[0049] Comparative Example 4 The difference from Example 1 is that, Step A2 is: coating the polymer electrolyte slurry on a template, performing a standing treatment (without magnetic field assistance), and performing a vacuum drying treatment to obtain a polymer electrolyte membrane; wherein the material of the template is polytetrafluoroethylene, the thickness of the polymer electrolyte membrane is 20 μm, the standing treatment time is 12 h, and the vacuum drying treatment temperature is 60°C, and the time is 12 h.

[0050] Step A3 is: the polymer electrolyte membrane and the lithium metal are pressed together by a hot isostatic pressing method in a top-to-bottom arrangement to obtain a polymer electrolyte membrane modified lithium metal; wherein the solid-state electrolyte is Li6PS5Cl.

[0051] Step A4 is: the polymer electrolyte membrane modified lithium metal is used as a negative electrode, LiNi 0.8 Co 0.1 Mn 0.1 O2 is used as a positive electrode active material, and Li6PS5Cl is used as a solid-state electrolyte to assemble a full-solid-state lithium battery.

[0052] Comparative Example 5 The polymer, the metal organic acid salt, the plasticizer, and the lithium salt are dissolved in an organic solvent to obtain a polymer electrolyte slurry; wherein the mass of the polymer is 1 g, the mass of the metal organic acid salt is 0.1 g, the mass of the plasticizer is 0.2 g, and the mass of the lithium salt is 362 mg; wherein the polymer is polyethylene oxide, the metal organic acid salt is Al(CF3SO3)3, the plasticizer is butanedinitrile, and the lithium salt is lithium bis-trifluoromethanesulfonimide; the organic solvent is anhydrous acetonitrile, and the amount used is 25 ml.

[0053] The polymer electrolyte slurry is coated on the lithium metal, and a vacuum drying treatment is performed to obtain a polymer electrolyte membrane modified lithium metal; which is used as a negative electrode, LiNi0.8 Co 0.1 Mn 0.1 O2 is used as the positive electrode active material and Li6PS5Cl is used as the solid electrolyte to assemble an all-solid-state lithium battery.

[0054] Experimental example The solid-state lithium batteries prepared in Example 1 and Comparative Example 1 were subjected to 100 charge and discharge cycle tests and the surface morphology of the lithium metal was characterized by scanning electron microscopy. Figure 1 and Figure 2 ,from Figure 1 It can be seen that the lithium metal surface deposited layer in Example 1 is flat and has a dense structure without obvious dendrites. Figure 2 It can be seen that in Comparative Example 1, obvious dendritic deposits appear on the surface of the lithium metal, gully-like depressions exist in local areas, and the deposited layer is relatively rough.

[0055] The ionic conductivity of the polymer electrolyte membranes prepared in Examples 1 to 4 and Comparative Examples 2 to 5 was tested, and the results are shown in Table 1. As can be seen from Table 1, compared with Comparative Examples 2 and 3, the ionic conductivity of the polymer electrolyte membranes prepared in Examples 1 to 4 is higher, which can make the ion transport performance of the solid electrolyte / lithium metal interface better; the interface impedance of the modified lithium metal prepared in Examples 1 to 4 and Comparative Examples 1 to 5 is tested, and the results are shown in Table 1. As can be seen from Table 1, compared with Comparative Examples 1 to 5, the interface impedance of the modified lithium metal prepared in Examples 1 to 4 is lower, indicating that the ion transport performance of the solid electrolyte / lithium metal interface is better. The capacity retention rate of the solid-state lithium batteries prepared in Examples 1 to 4 and Comparative Examples 1 to 5 was tested after 100 charge and discharge cycle tests. The results are shown in Table 1. Compared with the solid-state lithium batteries prepared in Comparative Examples 1 to 5, the capacity retention rate of the solid-state lithium batteries prepared in Examples 1 to 4 is higher, indicating better cycle performance.

[0056] Table 1

[0057] It should be noted that Comparative Example 1 does not involve a polymer electrolyte membrane, and the "-" in Table 1 indicates no data. It should be noted that the modified lithium metal in Comparative Examples 2, 3, and 4 refers to lithium metal modified with a polymer electrolyte membrane, the modified lithium metal in Comparative Example 5 refers to lithium metal modified with a polymer slurry, and the modified lithium metal in Examples 1 to 4 refers to lithium metal modified with a gradient SEI.

[0058] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A method for preparing a polymer electrolyte membrane, characterized in that: include: Step S1, dissolving a polymer, a metal organic acid salt, a plasticizer and a lithium salt in an organic solvent to obtain a polymer electrolyte slurry; Step S2: coating the polymer electrolyte slurry on a template, allowing it to stand under an external magnetic field, and then performing vacuum drying to obtain a polymer electrolyte membrane; wherein the direction of the external magnetic field is perpendicular to the template.

2. The method of claim 1, wherein: In the step S1, the mass ratio of the polymer, the metal organic acid salt, the plasticizer and the lithium salt is (95 to 100): (8 to 12): (18 to 22): (30 to 40).

3. The method of claim 1, wherein: In the step S1, the metal ions in the metal organic acid salt include Mg 2+ 、Al 3+ 、In 3+ 、Zn 2+ 、Ag + 、Sn 4+ 、Au + , Pt + 、Ge 4+ 、Bi 3+ and Sb 3+ At least one of; the organic acid radical in the metal organic acid salt includes at least one of sulfonate, fluorosulfonate, trifluoromethanesulfonate, fluorosulfonimide, tris(pentafluorophenyl)borate and tris(trifluoromethyl)borate.

4. The method of claim 1, wherein: In the step S1, the polymer includes at least one of polyethylene oxide, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, polyvinyl chloride, polyurethane and polyimide.

5. The method of claim 1, wherein: The plasticizer includes at least one of succinonitrile, adiponitrile, glutaronitrile, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, N-butyl-N-methylpyrrolidino bis(fluorosulfonyl)imide salt, tetraethylammonium trifluoromethanesulfonate, ethylene carbonate, propylene carbonate, fluoroethylene carbonate, diethylene glycol dimethyl ether, perfluoropolyether and polyethylene glycol dimethyl ether.

6. The method of claim 1, wherein: In step S1, the lithium salt includes at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium trifluoromethylsulfonate, lithium dioxalatoborate, and lithium difluorooxalatoborate.

7. The method of claim 1, wherein: In step S2, the magnitude of the external magnetic field is 0.1T to 0.5T.

8. The method of claim 1, wherein: In the step S2, the standing treatment time is 10 hours to 14 hours, and the vacuum drying treatment temperature is 50° C. to 70° C., and the time is 10 hours to 14 hours.

9. A polymer electrolyte membrane, characterized in that The polymer electrolyte membrane is manufactured by the method according to any one of claims 1 to 8.

10. Use of the polymer electrolyte membrane according to claim 9, characterized in that: include: The polymer electrolyte membrane and lithium metal are pressed together to obtain modified lithium metal.

Citation Information

Cited By

  • Polymer solid electrolyte, preparation method and application thereof

    CN122436563A

  • Polymer solid electrolyte, preparation method and application thereof

    CN122436563B